2021
DOI: 10.3390/ijerph18073484
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Oxygen Desaturation and Re-Saturation Capacity Limits in Repeated Sprint Ability Performance in Women Soccer Players: A New Physiological Interpretation

Abstract: Muscle oxygen consumption could provide information on oxidative metabolism in women soccer players. Therefore, the objective of this study was to analyze muscle oxygenation dynamics during repeated sprint ability (RSA): (8 sprint × 20 s recovery) by near-infrared spectroscopy (NIRS). The sample was made up of 38 professional women soccer players. To measure the external load, the best time, worst time, average time, individual speed, sprint decrement, and power were assessed. In connection with the internal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Through such treatment, we were able to narrow down the problem. Similarly, studies have not reported measurement problems using this methodology [ 31 , 32 ]. The contribution of our study is that it presents the difference of work in VT1 and VT2 with SmO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Through such treatment, we were able to narrow down the problem. Similarly, studies have not reported measurement problems using this methodology [ 31 , 32 ]. The contribution of our study is that it presents the difference of work in VT1 and VT2 with SmO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 20:40 induced a more complete reoxygenation during recovery phase (i.e., lower [HHb] min and higher [tHb] max) compared with 5:10 and 10:20. This would suggest a greater inhibitory effect of the nitric oxide on vascular vasoconstriction, inducing a larger hyperemia (40). The higher metabolite (K + , lactate) accumulation during 20:40 may contribute to both vasorelaxation and hyperemia (41).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first research paper comparing SmO 2 responses in speed skaters between two different types of exercise tests. Previous studies ( Buchheit and Ufland, 2011 ; Nagasawa, 2013 ; Paquette et al, 2020 ; Vasquez-Bonilla et al, 2021 ) examined recovery following WAnT and short-term efforts in kayak and football players, or the rate of reoxygenation following maximal aerobic exercise test ( Ichimura et al, 2006 ). One of the study’s limitations is the differences in baseline SmO 2 values found among speed skaters could be due to the slightly different phase of measurement, i.e., 2 min after the warm-up in WAnT (affecting better blood supply and muscle oxygenation) and at rest before GXT, ( Figure 1 ) or slight position change of the NIRS device.…”
Section: Discussionmentioning
confidence: 99%